Antitheilerial Activity of the Anticancer Histone Deacetylase Inhibitors - Barman, Madhumanti; Kamble, Sonam; Roy, Sonti; Bhandari, Vasundhra; Singothu, Siva; Dandasena, Debabrata; Suresh, Akash; Sharma, Paresh (Frontiers in Microbiology, 2021)
The apicomplexan parasite, Theileria annulata, is the most prevalent hemoprotozoan in livestock, causing significant economic losses worldwide. It is essential to develop new and improved therapeutics, as current control measures are compromised by the development of resistance against the only available antitheilerial drug, buparvaquone (BPQ). Histone deacetylase inhibitors (HDACi) were shown to treat cancer effectively and revealed in vitro antiparasitic activity against apicomplexan parasites such as Plasmodium and Toxoplasma. In this study, we investigated the antitheilerial activity of the four anti-cancer HDACi (vorinostat, romidepsin, belinostat, and panobinostat) against the schizont stage of T.annulata parasites. All four HDACi showed potent activity and increased hyperacetylation of the histone-4 protein. However, based on the low host cell cytotoxicity and IC50 values, vorinostat (0.103 µM) and belinostat (0.069µM) were the most effective showing antiparasitic activity. The parasite-specific activities of the HDACi (vorinostat and belinostat) were evaluated by western blotting using parasite-specific antibodies and in silico analysis. Both vorinostat and belinostat reduced the Theileria infected cell viability by upregulating anti-apoptotic proteins and mitochondrial dysfunction, leading to caspase-dependent cell apoptosis. The HDACi caused irreversible and antiproliferative effects on the Theileria infected cell lines. Our results collectively showed that vorinostat and belinostat could be used as an alternative therapy for treating Theileria parasites.